Membuka Kompleksitas Kesehatan: Kajian Komprehensif Penerapan Systems Thinking dalam Organisasi Kesehatan Modern : Literature Review - Yoga Saputra; Dede Efendy; Mona Valentin Br. Tambunan; Ferdy Ferdy (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the application of systems thinking in modern healthcare organizations, with a particular focus on Peter Senge’s Fifth Discipline. Using a systematic literature review of 20 selected articles, the study investigates the potential and challenges of applying systems thinking across key areas such as patient safety, service integration, resource management, and innovation. Findings indicate that systems thinking provides a holistic framework to better understand and address the inherent complexity of healthcare systems. By fostering interconnections among organizational components, it enhances the capacity to improve performance, ensure patient-centered care, and support sustainable change. Nevertheless, implementation is hindered by obstacles such as resistance to change, lack of shared understanding, and difficulties in measuring systemic outcomes. To address these barriers, the study highlights strategies including leadership development, staff training, and the establishment of appropriate evaluation tools. These measures strengthen organizational readiness and support a culture of continuous learning. The study concludes that systems thinking offers valuable insights for healthcare organizations to adapt to evolving challenges, but its success requires long-term commitment, supportive leadership, and systematic implementation. Future research should further explore the integration of systems thinking with emerging digital health technologies and assess its long-term impact on health outcomes and organizational resilience.